Multiparity In Timor-Leste, Risk Factor Associate the Midwife Intervention in Center Health of Community Ainaro Timor-Leste - Carvalho de Araujo, Eugenia; da Costa Monteiro, Ermelinda; Pereira, Natalia; de Deus, Elisa; Jose Tilman, Etelvina (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: East Timor has changed dramatically. Since its independence just a decade ago, it has a post-conflict country to a developing country to lower middle-income. As the country experienced the socio-economic progress and security in recent years, multiparity situation in Timor-Leste has also gradually improved. However, there are several challenges that still affect many children born in the same family in East Timor. The analysis of the overall situation of the family having many children is imperative to ensure evidence-based actions to address the remaining challenges in the country's changing context. Objective: The objective of this thesis is to know the factors of multiparity; Identify the knowledge of women about the risk of multiparity; Knowing what the perception of women on the intervention of the midwife in the risk of Multiparity. Method: This research is a study of exploratory and descriptive. The sample is composed of 30 pregnant women who attended antenatal Ainaro Health Center in the central part of East Timor. The data collection collected in the period from 5 October to 6 November 2015. Result and Discussion: Multiparity provides strong reasons such as assisting a family continuation of generations, care for the parents when they are elderly. Conclusion: This study indicates that, although few women in Ainaro district are aware that there are dangers associated with high birth, but most of our respondents do not think that there are health risks associated with having many children. With their education, they think that high birth women feel that having many children was harmless to your health. This number is significant, considering the implications of high parity on maternal and neonatal morbidity and mortality and long-term, socio - economic. This is more so when viewed considering a total of high fertility in East Timor in an economy that is not developed